Mechanisms of exercise in the treatment of lung cancer – a mini-review - Luo, Zhiwen; Wan, Renwen; Liu, Shan; Feng, Xinting; Peng, Zhen; Wang, Qing; Chen, Shiyi; Shang, Xiliang (Frontiers in Immunology, 2023)
Lung cancer constitutes a formidable menace to global health and well-being, as its incidence and mortality rate escalate at an alarming pace. In recent years, research has indicated that exercise has potential roles in both the prevention and treatment of lung cancer. However, the exact mechanism of the coordinating effect of exercise on lung cancer treatment is unclear, limiting the use of exercise in clinical practice. The purpose of this review is to explore the mechanisms through which exercise exerts its anticancer effects against lung cancer. This review will analyze the biological basis of exercise's anticancer effects on lung cancer, with a focus on aspects such as the tumor microenvironment, matrix regulation, apoptosis and angiogenesis. Finally, we will discuss future research directions and potential clinical applications.